Young Farmers’ Cooperation Behavior and the Role of Social Media in Developing Agribusiness - Widhiningsih, Diah Fitria; Hariadi, Sunarru Samsi (KnE Social Sciences, 2019)
In conducting agribusiness, young farmers are connected with each other in a farmer group. Cooperation becomes the major requirement for maintaining their existence. Furthermore, in the digital era, many people use the internet to help their work and present it to the public through social media. Additionally, to develop their agribusiness, young farmers develop good relationships with extension workers who assist them and connect them to the government. Meanwhile, the government develops policies and supporting materials for young farmers such as fertilizer. Therefore, based on this phenomenon, this quantitative research is aimed at understanding young farmers’ cooperation behavior, especially in using social media in supporting their agribusiness and whether there is difference in cooperation between those utilizing social media and those who do not. It employed 39 young farmers in Kalasan and Prambanan Subdistrict who plant chili as horticulture commodities. It showed that young farmers’ cooperation was described in their activities on seedling, irrigation, crops maintaining, and marketing, but their cooperation practice was not high. On the other hand, they did not always use social media and Kolmogorov Smirnov’s analysis resulted that there was not any difference in cooperation practice due to the social media application. Moreover, not all of them were familiar with social media in the implementation of agribusiness. In this case, they need more assistance from extension workers so they should introduce social media as part of agribusiness to all of young farmers through agricultural extensions to connect young farme the worldwide. Keywords: Young Farmers’ Cooperation, Social Media on Agribusiness, Agricultural Extension, Extension Workers